The Influence Of Taxpayer Awareness And Tax Supervision on Collection Efficacy Of Rural and Urban Land and Building Tax (PBB-P2) in Gorontalo City - Katili, Adriyun; Irigisa, Irawaty; Pakaya, Abdul Rahman (Universitas Negeri Medan, 2020)
This research aims at finding out the partial and simultaneous influence of taxpayer awareness and tax supervision on collection efficacy of rural and urban land and building tax (PBB-P2) in GorontaloCity. This research applies a quantitative approach using the expost facto method. The research design is causality. The technique of data analysis uses multiple regression. Findings revealed that (1) taxpayer awareness has a positive and significant influence on PBB-P2, (2) tax supervision has a positive and significant influence on PBB-P2, and (3) taxpayer awareness and tax supervision simultaneously have a positive and significant influence on PBB-P2 with 33.20% of the determinant value. Furthermore, the remaining 66.80% value is influenced by other variables that are not explained in this research such as taxpayer discipline, tax sanction, taxpayer compliance, reward for tax authorities, commitment, tax authority competency, and administrative modernization of PBB-P2